10.1016/s0029-7437(05)70837-5 (CrossRef Listing of Deleted DOIs, 2000)
The rhizosphere is a key ecological niche where plants interact with microorganisms, and its health directly affects plant growth, development, and disease resistance. Existing theories have laid an important foundation for understanding plant-microbe interactions. Among them, the biological market theory interprets the mutualistic symbiosis between plants and microorganisms from the perspective of nutrient exchange, offering valuable insights into resource flow and interaction mechanisms within the rhizosphere. On this basis, this study further proposes the conceptual model of 'biological corporation' to integrate interaction mechanisms covering three dimensions: plant-dominated regulation, microbial functional differentiation, and signal network coordination. Within this theoretical framework, plants modulate the screening and colonisation of microbial communities via a dual-genome regulatory system. Microbial populations reshape community structure and drive functional differentiation through resource competition, cross-feeding symbiosis, and defensive strategies. Interkingdom and intrakingdom signal cascades further link the physiological and metabolic processes of plants and microorganisms, thereby facilitating the steady-state maintenance of the rhizosphere microecosystem. Based on this hierarchical symbiotic mechanism, we propose a three-step regulatory scheme for rhizosphere health restoration, and provide practical strategies including crop germplasm improvement, synthetic microbial consortium construction, and cross-kingdom signal engineering to mitigate combined biotic and abiotic stresses in farmland.